As Marias de Rachel de Queiroz: trajetórias e dilemas femininos no romance as Três Marias - Oliveira, Joana Angélica Travassos de (2017)
The present dissertation has as its main corpus of analysis the novel As três Marias (1939), by the Brazilian writer Rachel de Queiroz (1910-2003). It aims at investigating the feminine figurations created in the book, by observing the trajectory of the three main characters in the narrative plot: Maria Augusta, Maria José and Maria da Glória, three girls who meet one another in a boarding school run by nuns and soon begin a lifelong friendship. Firstly, there’s a contextualization of the author’s literary career, the very first woman to take part in the Brazilian Academy of Letters. Then, we advance towards the description of some of the strong female characters the author usually portrays in her books, in an attempt to situate the novel “As três Marias” in her body of work. Finally, we analyze the trajectory of the three Marias, by examining the main character’s narrative voice, Guta, short for Maria Augusta, who incarnates women’s struggle for emancipation and their fight against suppression. Moreover, this research seeks to analyze the way three different roles of women, emblematic of the Brazilian society in the first half of the twentieth century, are depicted in the novel: women confined to marriage and family (Maria da Glória), women who join religion and pursue a career in teaching (Maria José), and those who seek freedom and independence, breaking the stereotype of submissive and dominated women in a patriarchal society (Guta)